PENGARUH KESADARAN EKOLOGI PADA NIAT PEMBELIAN KONSUMEN MUDA - Jayadi; Syamsuddin; Nur Aini; Adinda Aprilia (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research reveals a positive relationship between Green Packaging Awareness, Social Value, and Emotional Value with Consumer Attitudes. The findings indicate that Emotional Value exerts a stronger influence on Consumer Attitudes compared to Green Packaging Awareness and Social Value. Consequently, companies and organizations may prioritize developing strategies to enhance the Emotional Value associated with their products or services. Furthermore, the enhancement of Consumer Attitudes toward green packaging, Social Value, and Emotional Value was also found to positively contribute to Purchase Intention. Therefore, companies and organizations can conclude that efforts to improve these factors can boost consumers’ intent to purchase the offered products or services. This study provides valuable insights into understanding and leveraging Green Packaging Awareness, Social Value, and Emotional Value to enhance consumer relationships and drive their purchase intent. The practical implications of these findings underscore the importance of building emotional connections with consumers, which can be a key success factor in marketing sustainable products and services